East Canadian Arctic Kayak - Arima, Eugene (ARCTIC, 1990)
This profile discusses the various designs of the East Canadian Arctic kayak. Several main regional styles are distinguished as North Baffin, northwest Greenland (c. 1860-1930), East and South Baffin and north Labrador, Atlantic Labrador, and West Labrador; finer distinctions are also possible. Although they vary considerably in size and shape, these kayaks share a recognizable basic pattern, with a long, rising bow, low stern, wide, flat deck and narrower bottom, usually but not always flat. Load capacity varied but was comparatively great given the ample hull volume, with displacement increasing quickly from the flared sides as the waterline rose. Various uses and hunting methods and utensils are also described. However the origins of the early kayaks arose, the East Arctic kayak was well suited to its use and provided the Inuit a vital edge in their hunting pursuits.